THE IMPORTANCE OF THE LATIN LANGUAGE AND OF ROMAN LAW FOR DEVELOPMENTS IN EUROPEAN LAW – ILLUSTRATED FOR PROPERTY ACQUISITION - Franz-Rudolf Herber (European Scientific Journal, ESJ, 2013)
Property is one of the fundaments of ancient, medieval and modern society; the relevant legislation is of eminent importance and is still dominated by principles of Roman law: – The so-called abstraction principle is applied Roman law: It separates the contractual agreement and the acquistion of property. If the contractual agreement is invalid, there is given a so-called >condictio indebiti<, even if the translation of property is valid. – The acquisition of property in good faith is based on Roman law; the prinicple of acquisition in good faith protects the legal relations and postpones the interest of the (former) owner. – The relationships between the property owner and the unrightful possessor may be rather intricated, Roman law gives the answers. Roman law was the private international law that ruled the legal transactions of civil life. The European Union is on the way for more unification of civil law in its member states, but there is still a very long distance to go – the way is rather stony, because the member states are in some espects fixed on their own codified civil law. This way is stony, because there is no lingua franca in the European Union: The success of Roman law was based on the success of the Latin language, whose grammar, syntax and phonology is rather easy. Latin was the lingua franca of the ancient Europe, of the medieval Europe and in the further sequence up to the Enlightenment, whereas the European Union has as many official languages as it has member states. Nevertheless, the Latin language is not dead and the Roman law is not outdated.